Viewpoint. Reflexions about contemporary issues on scientific publications in health: excerpts from the inaugural talk for the PhD in Health at Universidad del Valle - Ridde, Valéry (Revista Estomatología, 2016)
As part of the launch of the health doctorate program in the Faculty of Health at Universidad del Valle, in Cali on June 17, 2015, a talk on the publishing system for scientific articles was delivered. In this viewpoint, it is expected to share some reflections on this system, its characteristics, quirks, and modern-day developments. Not only students embarking on a health doctorate, but also early-career researchers, need to be properly trained and more knowledgeable about this system, to be able to adapt themselves appropriately and strategically. In this text, we address issues of authorship, peer review, predatory journals, and open access. We also discuss promising new initiatives to improve the publication system, notably with respect to the research community’s evaluation system, which is largely responsible for the observed shortcomings.